EDUKASI PENCEGAHAN COVID-19 DENGAN METODE 5M PADA REMAJA DESA SIDOREJO KABUPATEN SUKOHARJO - W Wahyuni; Siti Fatmawati; Tutik Yulianti (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Covid-19 can be transmitted from one individual to another through coughing/sneezing droplets (droplets). Besides that, people can also be infected by touching surfaces that have been contaminated with the Covid-19 virus and then touching their faces (eg eyes, nose and mouth). Through the implementation of physical distancing such as staying away from gatherings or crowds, avoiding mass gatherings, and keeping a distance from other people, you can reduce the risk of being infected with Covid-19 (or what we know as 5M (wearing masks, washing hands, keeping your distance, staying away from formulas, reducing mobility). The purpose of this service is to provide information to adolescents in preventing Covid-19, while the problems encountered in adolescents are not all adolescents know what prevention of Covid-19 is with the 5M method. Solutions offered increase knowledge and empower youth in preventing Covid-19, the method used used socialization and assistance to adolescents in preventing Covid-19 the results of the behavior of preventing covid-19 washing hands properly by 92.5%, wearing masks by 90%, maintaining distance by 87.5%, reducing mobility by 80% and avoiding crowds by 85% Conclusion Most of the 60% of teenagers are <20 years old, most of the teenagers are 70% with vocational/high school education, the behavior of preventing covid-19 is washing hands properly by 92.5%, wearing masks by 90%, keeping a distance by 87.5%, reducing mobility 80% and stay away from the crowd by 85%